1001 Little Parenting Miracles - Floyd, Esme (London Carlton, 2008)
From calming a new born baby and dealing with toddler tantrums to fussy eating and teenage angst, 1001 Little parenting Miracles offers advice on all parenting dilemmas. Crammed full of facts, tips and strategies, this book will soon set you on the road to a more enjoyable and fraught-free family life
Include Color Illustration and Index
Keywords: Parenting -- Child development -- Child psychology